Non-genomic Actions of Methylprednisolone Differentially Influence GABA and Glutamate Release From Isolated Nerve Terminals of the Rat Hippocampus - Neiva, Rafael; Caulino-Rocha, Ana; Ferreirinha, Fátima; Lobo, Maria Graça; Correia-de-Sá, Paulo (Frontiers in Molecular Neuroscience, 2020)
Corticosteroids exert a dual role in eukaryotic cells through their action via (1) intracellular receptors (slow genomic responses), or (2) membrane-bound receptors (fast non-genomic responses). Highly vulnerable regions of the brain, like the hippocampus, express high amounts of corticosteroid receptors, yet their actions on ionic currents and neurotransmitters release are still undefined. Here, we investigated the effect of methylprednisolone (MP) on GABA and glutamate (Glu) release from isolated nerve terminals of the rat hippocampus. MP favoured both spontaneous and depolarization-evoked [14C]Glu release from rat hippocampal nerve terminals, without affecting [3H]GABA outflow. Facilitation of [14C]Glu release by MP is mediated by a Na+-dependent Ca2+-independent non-genomic mechanism relying on the activation of membrane-bound glucocorticoid (GR) and mineralocorticoid (MR) receptors sensitive to their antagonists mifepristone and spironolactone, respectively. The involvement of Na+-dependent high-affinity EAAT transport reversal was inferred by blockage of MP-induced [14C]Glu release by DL-TBOA. Depolarization-evoked [3H]GABA release in the presence of MP was partially attenuated by the selective P2X7 receptor antagonist A-438079, but this compound did not affect the release of [14C]Glu. Data indicate that MP differentially affects GABA and glutamate release from rat hippocampal nerve terminals via fast non-genomic mechanisms putatively involving the activation of membrane-bound corticosteroid receptors. Facilitation of Glu release strengthen previous assumptions that MP may act as a cognitive enhancer in rats, while crosstalk with ATP-sensitive P2X7 receptors may promote a therapeutically desirable GABAergic inhibitory control during paroxysmal epileptic crisis that might be particularly relevent when extracellular Ca2+ levels decrease below the threshold required for transmitter release.